Root biostimulation and solar irradiation in Coffea arabica L. nursery plants - Aguilar-Luna, Jesús Mao; Hernández-Vargas, Liliana; Hernández-Ángel, Rodolfo (Agronomía Mesoamericana, 2024)
Introduction. In the nursery stage, quality Coffea arabica L. plants can be developed, which reduces the stressful effects after transplanting, increases photosynthetic efficiency, and maintains a constant growth rate. Objective. To evaluate the effect of biostimulants and solar irradiation on the growth and physiology of Coffea arabica plants during the nursery stage. Materials and methods. The experiments were carried out in a greenhouse at the Benemérita Universidad Autónoma de Puebla, Mexico, over a period of 270 days, in 2018 and 2022. A factorial block design was used, with three factors: biostimulants (control, mycorrhizal fungi, seaweed, and organic polymers), irradiation (81, 168, 278 and 440 μmol m-2 s-1), and varieties (Costa Rica 95, Marsellesa, Caturra Roja and Garnica). Mycorrhizal colonization (MC), root system proportion (RSP), growth rate (GR), aerial proportion (AP), chlorophylls, and nutritional content were determined. An analysis of variance was performed on the data to detect differences between treatments. Results. At 270 days after sowing, the Marsellesa variety, biostimulated with mycorrhizal fungi and exposed to an irradiation of 168 ± 36 μmol m-2 s-1, reached higher values in MC with 36.51 %, and GR with 0.175 g g-1 day. In Costa Rica 95 and Marsellesa, biostimulation with polymers and an irradiation of 440 ± 59 μmol m-2 s-1 were significantly related (p ≤ 0.05) to increases of 3.08 mg g-1 FMW (fresh matter weight) in total chlorophyll. In Marsellesa, biostimulation with polymers and 168 ± 36 μmol m-2 s-1 irradiation resulted in higher contents of N, P, K, Ca, and Mg. Conclusions. Root biostimulation with mycorrhizal fungi and irradiation levels of 168 to 278 μmol m-2 s-1 led to better development in coffee plants.